Non-functioning neuroendocrine tumors of the common hepatic duct: a case report and literature review - Abou-Jaoude, Maroun; Nasser, Haydar A. (International Surgery Journal, 2017)
Extra-hepatic biliary tree neuroendocrine tumors are not common, accounting for about 0.1 % of all carcinoid tumors. Those affecting the common hepatic duct are very rare and their diagnosis is usually made post-operatively. Poorly differentiated tumors or neuroendocrine carcinomas are commonly seen in elderly, whereas well differentiated tumors, tend to occur in young patients, for whom surgery will lead to good long term results. About 100 cases have been reported in the English medical literature, showing good long term results after surgery for well differentiated (Grades 1 and 2) tumors. Herein, we report a case of an 18-year-old female, complaining from a dull epigastric pain related to a nodule compressing the common hepatic duct. After complete investigation, a laparotomy has been performed and showed a nodular tumor located in the common hepatic duct just above the insertion of the cystic duct with close contact with the pancreatic head distally. En bloc cholecystectomy with bile duct resection was performed and followed by a Roux-en-Y hepatico-jejunostomy. The pathology of the nodule came back to be a neuroendocrine tumor grade 2.